2022
DOI: 10.1038/s41387-022-00228-w
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and gene expression analysis in adipose tissue to identify new loci associated with T2D development in obesity

Abstract: Background Obesity is accompanied by excess adipose fat storage, which may lead to adipose dysfunction, insulin resistance, and type 2 diabetes (T2D). Currently, the tendency to develop T2D in obesity cannot be explained by genetic variation alone—epigenetic mechanisms, such as DNA methylation, might be involved. Here, we aimed to identify changes in DNA methylation and gene expression in visceral adipose tissue (VAT) that might underlie T2D susceptibility in patients with obesity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…To delimit DMCs with a correlation between DNA methylation level and BMI, a Pearson's correlation was performed with a bootstrap analysis with the Boot package, to select only robust associations, as previously described. [33,34] The same approach was applied to correlate the methylation levels of the DMCs with the other post-surgical clinical parameters.…”
Section: Methodsmentioning
confidence: 99%
“…To delimit DMCs with a correlation between DNA methylation level and BMI, a Pearson's correlation was performed with a bootstrap analysis with the Boot package, to select only robust associations, as previously described. [33,34] The same approach was applied to correlate the methylation levels of the DMCs with the other post-surgical clinical parameters.…”
Section: Methodsmentioning
confidence: 99%
“…By examining the DNAm profiles of individuals with T2D, researchers have identified novel candidate genes associated with T2D and enhanced comprehension of the disease's pathogenesis 72 . Obesity primarily leads to the development of T2D by inducing IR and disrupting lipid metabolism.…”
Section: Dnam In Obesity‐associated Diseasesmentioning
confidence: 99%
“…59 According to Baca et al, obesity is associated with changes in DNA methylation and gene expression specific among different fat tissue depots, including EHD2. 60 At the same time, individuals who are obese show minimal expression of EHD2, and GLUT4 endocytosis into adipocytes increased, 49 suggesting that the regulation of caveolar dynamics by EHD2 may play a role in the development of obesity. 58 During the differentiation process of adipocytes, once triglycerides accumulate, the expression of EHD2 protein is highly upregulated.…”
Section: The Role Of Ehd2 In Lipid Uptake and Metabolismmentioning
confidence: 99%
“…80 Baca et al found that EHD2 is one of the epigenetic genes that exhibit DNA methylation and gene expression abnormalities in obese and type 2 diabetes patients and is significantly correlated with blood glucose and HbA1c levels. 60 In addition, EHD2 can stabilize caveolae on the membrane, while the loss of caveolae leads to lipodystrophic diabetes in humans. 81 In addition, EHD2 has been shown to regulate the trafficking of GLUT4, which is essential for glucose uptake in insulin-sensitive tissues such as skeletal muscle and adipose tissue.…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation